2022
DOI: 10.1038/s41467-022-30239-1
|View full text |Cite
|
Sign up to set email alerts
|

Spindle motility skews division site determination during asymmetric cell division in Physcomitrella

Abstract: Asymmetric cell division (ACD) underlies the development of multicellular organisms. In animal ACD, the cell division site is determined by active spindle-positioning mechanisms. In contrast, it is considered that the division site in plants is determined prior to mitosis by the microtubule-actin belt known as the preprophase band (PPB) and that the localization of the mitotic spindle is typically static and does not govern the division plane. However, in some plant species, ACD occurs in the absence of PPB. H… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…4). It has previously been shown that the positioning of cell division planes in emerging gametophores is dependent on microtubules (Kosetsu et al, 2017; Kozgunova et al, 2022). Thus, it is likely that the cell division orientation defects observed in the nog1dis mutant are due to aberrant organisation of the microtubule cytoskeleton.…”
Section: Discussionmentioning
confidence: 99%
“…4). It has previously been shown that the positioning of cell division planes in emerging gametophores is dependent on microtubules (Kosetsu et al, 2017; Kozgunova et al, 2022). Thus, it is likely that the cell division orientation defects observed in the nog1dis mutant are due to aberrant organisation of the microtubule cytoskeleton.…”
Section: Discussionmentioning
confidence: 99%
“…Within the cell wall biogenesis class are genes encoding cellulose synthase genes, notably PpCESA5 , mutations in which cause major defects in 3D growth (Goss et al., 2012 ). Many genes linked to the cell cycle and setting of cell division sites are also uniquely downregulated in PpTPL2 N176H [+] (Table S3 ), including genes belonging to the PpTPX2 family that are required for the orientation of the cell division plane early in 3D development (Kozgunova et al., 2022 ). Changes in the expression of specific genes, or general misregulation of the cell cycle, may conceivably disrupt the reprogramming of new cell identities (Ishikawa et al., 2011 ), contributing to the defects in both the transition to 3D growth and the formation of caulonemata in PpTPL2 N176H [+] plants.…”
Section: Discussionmentioning
confidence: 99%
“…However, little is known about the spatial control of acentrosomal MTOCs in plants. The apical cap of the moss protonema represents a form of MTOC that requires g-tubulin and TPX2 for formation and functions in early phase of mitosis as the major source of spindle microtubules (Kozgunova et al, 2022;Nakaoka et al, 2012). The current study demonstrates that SUN2 is required for the association between MTOCs and NE.…”
Section: Physcomitrella Sun2 Couples Ne With Microtubulesmentioning
confidence: 99%